Halogen‐Imparted Reactivity in Lithium Carbenoid Mediated Homologations of Imine Surrogates: Direct Assembly of bis‐Trifluoromethyl‐β‐Diketiminates and the Dual Role of LiCH2I. Issue 47 (9th September 2020) - Ielo, Laura; Castoldi, Laura; Touqeer, Saad; Lombino, Jessica; Roller, Alexander; Prandi, Cristina; Holzer, Wolfgang; Pace, Vittorio
Abstract: The selective formal insertion (homologation) of a carbon unit bridging the two trifluoroacetamidoyl chlorides (TFAICs) units is reported. The tactic is levered on a highly chemoselective homologation–metalation–acyl nucleophilic substitution sequence which precisely enables to assemble novel trifluoromethylated β‐diketiminates within a single synthetic operation. Unlike previous homologations conducted with LiCH2 Cl furnishing aziridines, herein we exploit the unique capability of iodomethyllithium to act contemporaneously as a C1 source (homologating effect) and metalating agent. The mechanistic rationale grounded on experimental evidences supports the hypothesized proposal and, the structural analysis gathers key aspects of this class of valuable ligands in catalysis. Abstract : The treatment of a trifluoroacetimidoyl chloride (TFAIC) with the carbenoid iodomethyllithium results in the chemoselective formation of a bis‐trifluoromethyl‐β‐diketiminate. This sequential two‐events strategy involves the homologation of the imine surrogate followed by the lithiation of the intermediate operated by the same carbenoid and attack of a second TFAIC unit.